Who Owns the Parliamentary Seat? Party Sovereignty, Legislative Recall, and Republican Justice in Indonesia’s Democracy - Sultoni Fikri; Imranullah Akhtar (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
The mechanism of Pergantian Antar Waktu (PAW) for legislators in Indonesia reflects a structural tension between popular sovereignty and party sovereignty. Although constitutionally recognized, PAW in practice is predominantly initiated and controlled by political parties, often without the involvement or consent of voters. This raises a fundamental constitutional problem concerning the erosion of representative freedom and the subordination of voters’ political will to internal party interests. Within a democratic constitutional, such a configuration invites critical scrutiny, particularly when assessed through normative theories of justice and freedom. This study aims to critically examine the legal construction and implementation of party-initiated PAW and to assess its compatibility with the principles of republican justice. The research seeks to demonstrate how PAW operates as a mechanism of arbitrary power that undermines the representative mandate and weakens popular sovereignty. This research employs legal research with a statutory approach and a conceptual approach. The study finds that party-initiated PAW institutionalizes a form of structural domination, where legislators and voters are placed in a condition of dependency on party discretion. The absence of public participation and effective accountability mechanisms renders PAW an exercise of arbitrary power incompatible with republican freedom. The novelty of this research lies in its application of Philip Pettit’s republican justice theory to Indonesian constitutional law, offering a critique that reconceptualizes PAW not merely as a procedural issue, but as a constitutional injustice rooted in domination over popular political will.